MAPPING THE S-WAVE VELOCITY STRUCTURE WITH SV-COMPONENT RECEIVER FUNCTION METHOD - Zou Z.; Chen X. (My University, 2003)
In this article, we analyze the characters of SV-component receiver function of teleseismic body waves and its advantages in mapping the S-wave velocity structure of crust in detail. Similar to radial receiver function, SV-component receiver function can be obtained by directly deconvolving the P-component from the SV-component of teleseismic recordings. Our analyses indicate that the change of amplitude of SV-component receiver function against the change of epicentral distance is less than that of radial receiver function. Moreover, the waveform of SV-component receiver function is simpler than the radial receiver function and gives prominence to the PS converted phases that are the most sensitive to the shear wave velocity structure in the inversion. The synthetic tests show that the convergence of SV-component receiver function inversion is faster than that of the radial receiver function inversion. As an example, we investigate the S-wave velocity structure beneath HIA station by using the SV-component receiver function inversion method.
Keywords: receiver function; SV-component receiver function; S-wave velocity structure inversion